Geoengineering site characterization for foundation integrity assessment. Issue 1 (1st January 2020) - Oyeyemi, K. D.; Olofinnade, O.M.; Aizebeokhai, A. P.; Sanuade, O. A.; Oladunjoye, M. A.; Ede, A. N.; Adagunodo, T. A.; Ayara, W. A.
Abstract: Inefficient near-surface characterizations prior to building construction have largely contributed to the incessant building failures in the form of structural defects and building collapses recently occurring in southern parts of Nigeria. Combined geophysical and geotechnical investigations have been used to select suitable foundation type and depth at a building construction site in part of the Lagos Island, Nigeria. Three geoelectrical resistivity survey profiles of length 150 m each were conducted using minimum and maximum electrode spacing of 5.0 m and 45.0 m, respectively. Boring, in-situ geomaterials samplings, cone penetrating tests, standard penetrometer tests and laboratory tests were among the geotechnical investigations carried out in accordance with the British standard code of practice. The geoelectrical resistivity imaging results provide the lateral and spatial spread of the geoelectrical units stratification within the study area, their clay and water contents. The results of the laboratory and geotechnical tests also reveal the subsoils lithologic units, their compressibility and shear strengths. A deeper pile-type foundation on a more competent stable subsoil stratum at the depth greater than 13 m is recommended for the proposed buildings in the study area so as to effectively transmit their loads.